Can we afford to forget the old killer (tuberculosis) in this COVID-19 pandemic: a case report of scrofula with COVID-19 in a health care worker - Lal, Roshan; Bhawani, Rajesh; Kumar, Nitesh; Bala, Jyoti; Chhopal, Sharab (International Journal of Research in Medical Sciences, 2021)
In the current scenario of COVID-19 pandemic, we are encountering COVID-19 patients with vague symptoms and in association with many other diseases. We are reporting such a case where neglecting other cause of pyrexia in a patient of COVID-19 would have resulted in disastrous consequences. A young 22 years aged female was admitted to our hospital as COVID-19 with right supraclavicular lymphadenopathy, she was subjected to FNAC of right supraclavicular lymph node. In RT-PCR Mycobacterium Tuberculosis was detected. After three days of starting on Antitubercular drugs she became afebrile. It is important to ensure early diagnosis and continuity of services for tuberculosis along with effective and rapid response to COVID-19 pandemic, so that anticipated increase in TB related deaths during this pandemic can be prevented.